Response of Eucalyptus pellita and Eucalyptus deglupta seedling growth to aluminum exposure - Salim, Mohammad Agus Salim; Setyaningsih, Luluk; Wahyudi, Imam; Budi, Sri Wilarso (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Aluminum (Al) is one of the problems and is a factor inhibiting plant growth on soils with acidic pH. This study aims to examine the growth response of Eucalyptus pellita and Eucalypus Deglupta seedlings to Al exposure. This study used a completely randomized design (CRD) with one factor, where the Al concentration consisted of 5 levels, namely: 0 mM (control), 2 mM, 4 mM, 6 mM, and 8 mM with 3 repetitions each and each repetition consisted of 3 units of the plant. The results showed that Al treatment had a significant effect on the growth parameters of both plant types, except for the root dry weight parameter for E. deglupta. Increasing the Al concentration can reduce almost all growth parameters. The 4 mM Al concentration was able to increase the height growth, plant dry weight (roots and shoots), and tolerance index for the E. pellita species, while the Al 2 mM concentration was able to increase the root growth of E. deglupta plants. Almost all growth parameters for E. pellita species were higher than that of E. deglupta, except for the SPAD chlorophyll index. The concentrations of 6 mM and 8 mM were toxic to E. pellita and E. deglupta.